The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1158/1078-0432.ccr-19-0955
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Antitumor Activity of a Binary EGFR/DNA–Targeting Strategy Overcomes Resistance of Glioblastoma Stem Cells to Temozolomide

Abstract: Purpose: Glioblastoma (GBM) is a fatal primary malignant brain tumor. GBM stem cells (GSC) contribute to resistance to the DNA-damaging chemotherapy, temozolomide. The epidermal growth factor receptor (EGFR) displays genomic alterations enabling DNA repair mechanisms in half of GBMs. We aimed to investigate EGFR/DNA combi-targeting in GBM.Experimental Design: ZR2002 is a "combi-molecule" designed to inflict DNA damage through its chlorethyl moiety and induce irreversible EGFR tyrosine kinase inhibition. We ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…As shown in Figure 2, the conversion of the combi-molecule AL530 into its two bioactive components (DNA damage species and MEK inhibitor) was largely accelerated at an acidic pH. The pH rate profile also indicated that AL530 is hydrolyzed at a pH range between 5.5-6.5, which is within the range of pH reported for the tumor microenvironment [12][13][14]. The results are in line with the cleavage mechanism proposed in Scheme 1, wherein the pH rate profile clearly suggests that N-protonation of the tetrahedral intermediate is the rate determining step of the reaction.…”
Section: Kinetics Of Al530 Hydrolysis At Variable Ph and Temperaturesupporting
confidence: 64%
“…As shown in Figure 2, the conversion of the combi-molecule AL530 into its two bioactive components (DNA damage species and MEK inhibitor) was largely accelerated at an acidic pH. The pH rate profile also indicated that AL530 is hydrolyzed at a pH range between 5.5-6.5, which is within the range of pH reported for the tumor microenvironment [12][13][14]. The results are in line with the cleavage mechanism proposed in Scheme 1, wherein the pH rate profile clearly suggests that N-protonation of the tetrahedral intermediate is the rate determining step of the reaction.…”
Section: Kinetics Of Al530 Hydrolysis At Variable Ph and Temperaturesupporting
confidence: 64%
“…However, resistant tumor cell subsets promoting recurrence, rapidly emerge. Although these cells, presenting CSC features, do frequently express EGFR, treatment with small molecules targeting the EGFR signal transduction pathway has proven largely disappointing, thus suggesting that direct immune-mediated targeting of this marker could be more effective (34). Our data indicate that, indeed, expansion of GBM-derived c-CSC may be prevented by ADCC mediated by CD16 158V -CR T cells and anti-EGFR IgG1 mAb.…”
Section: Discussionmentioning
confidence: 77%
“…For one patient, the cost decreases from 40 to 50% when using only the EGFR2/EGFR3 assay. Moreover, in contrast to FISH, dPCR allows the simultaneous detection of the EGFRvIII variant, which has been shown to be a potential therapeutic target [26]. Lower copy number values observed between EGFR2 and EGFR3 amplicons are very likely explained by the presence of the EGFRvIII variant.…”
Section: Discussionmentioning
confidence: 99%